2019
DOI: 10.1111/bph.14689
|View full text |Cite
|
Sign up to set email alerts
|

A photoswitchable GABA receptor channel blocker

Abstract: Background and Purpose Anion‐selective Cys‐loop receptors (GABA and glycine receptors) provide the main inhibitory drive in the CNS. Both types of receptor operate via chloride‐selective ion channels, though with different kinetics, pharmacological profiles, and localization. Disequilibrium in their function leads to a variety of disorders, which are often treated with allosteric modulators. The few available GABA and glycine receptor channel blockers effectively suppress inhibitory currents in neurons, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 62 publications
1
42
0
2
Order By: Relevance
“…A powerful alternative is using reversible chemical photoswitches to harness endogenous anion‐conducting receptor‐channels like GABA and glycine receptors (GABA A R, GlyR), which mediate inhibitory neurotransmission in the mammalian central nervous system . Although some GABA A R photoswitches have been reported based on azobenzene, this photochromic group displays several shortcomings: it provides incomplete photoconversion due to a substantial overlap of the absorption maxima of cis and trans isomers, and can alter the pharmacophore activity. Indeed, in all azobenzene derivatives of benzodiazepines (allosteric potentiators of GABA A R) this characteristic property is abolished, as found in the 7‐amino site of nitrazepam, which is reportedly tolerant of other substitutions .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…A powerful alternative is using reversible chemical photoswitches to harness endogenous anion‐conducting receptor‐channels like GABA and glycine receptors (GABA A R, GlyR), which mediate inhibitory neurotransmission in the mammalian central nervous system . Although some GABA A R photoswitches have been reported based on azobenzene, this photochromic group displays several shortcomings: it provides incomplete photoconversion due to a substantial overlap of the absorption maxima of cis and trans isomers, and can alter the pharmacophore activity. Indeed, in all azobenzene derivatives of benzodiazepines (allosteric potentiators of GABA A R) this characteristic property is abolished, as found in the 7‐amino site of nitrazepam, which is reportedly tolerant of other substitutions .…”
Section: Figurementioning
confidence: 99%
“…To characterize Fulgazepam in vitro, patch clamp experiments were performed on cells transiently expressing α 1 β 2 γ 2 subunits of the GABA A receptor. This receptor possesses the canonical benzodiazepine allosteric site and its EC 50 for GABA is about 8 μ m . The effects of the fulgimide‐based benzodiazepine derivatives 3 and 4 on the receptor's function were studied upon co‐application of 0.5 μ m GABA, that is, a concentration below the EC 50 (close to EC 3 ) that allows to observe allosteric potentiation of GABA A R‐mediated currents …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This receptor possesses the canonical benzodiazepine allosteric site and its EC50 for GABA is about 8 µM. [54] The effects of the fulgimide-based benzodiazepine derivatives 3 and 4 on the receptor's function were studied upon co-application of 0.5 µM GABA, i.e. the concentration, which is below the EC50 (close to EC3) and allows to observe allosteric potentiation of GABAAR-mediated currents.…”
Section: Photochromic Propertiesmentioning
confidence: 99%
“…It has been recently shown that Azo-NZ1, the azobenzene derivative of nitrazepam, blocks in a UV-dependent manner the ion channel pore of GABA A alpha1/beta2/gamma2 and GABA C rho2 receptors and controls GABAergic currents (Maleeva et al, 2019). These experiments also suggested that Azo-NZ1 is capable to modulate the activity of another subtype of Cys-loop receptors -alpha2 GlyR.…”
Section: Introductionmentioning
confidence: 98%